A Critical Analysis of the Form and Concept of Poems of Secondary High Schools Persian Literarute Books - Mohammad Aalizadeh Meresht; Ghodsieh Rezvanian; Samaneh Jafari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the curriculum of Iran, the Persian Literature lessons and its textbooks play a significant role. At the same time, poetry is very important in Persian literature. For these reasons, this paper intends to describe analytically the Persian Literature books of this period in a quantitative and qualitative way to examine the status of poetry and the intellectual and aesthetic approaches of the selected poems. We want to know if the poems in these books have the ability to portray an appropriate, transcendent, and realistic picture of Persian poetry in students’ minds. The results indicate that the books in question are mostly prose-based. The selected poems are mostly devoted to epic, patriotic and revolutionary literature, and from an intellectual and aesthetic point of view, they may not be attractive enough to encourage students to read and enjoy textbooks in class. Due to the inappropriate distribution of poems in literary genres, styles of poetry, poetry formats, and poems of Persian books, this course does not show the correct face of Persian poetry to the audience. In terms of the status of the poets and their works, there are also many criticisms of the three books. Therefore, this study emphasizes the necessity of revising and modifying the textbooks studied.